Next to the color line : gender, sexuality, and W.E.B. Du Bois - Gillman, Susan Kay; Weinbaum, Alys Eve, 1967- (Critical American studies series., 2007)
This provocative collection investigates how W.E.B. Du Bois approached gender and sexuality. The essays in Next to the Color Line not only reassess his politics but also demonstrate his relevance for today's concerns.